Analisis Tingkat Keuntungan Usahatani Padi Sawah sebagai Dampak dari adanya Subsidi Pupuk di Kabupaten Tabanan - NI LUH PRIMA KEMALA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstrak Agriculture is a sector that plays an important role in the welfare of the Indonesian population lives . As one of the pillars of the state economy , the agricultural sector is expected to increase the income of rural residents especially are still below the poverty line. For the various investments and policies have been taken by the government to encourage growth in the agricultural sector , one of them in the form of fertilizer subsidies. The research objective was to analyze the level of paddy rice farming profits as a result of the impact of the fertilizer subsidy in Tabanan. The results show the financial benefits of paddy farming in the dry season and the rainy season is Rp . 5,625,704.23 per ha and Rp . 5,802,663.42 per ha . R / C each season are 1.40 and 1.39 . Economic advantages in the dry season and the rain is Rp . 3,052,706.47 / ha and Rp 1,234,146.40 / ha , while the divergence of net profit was Rp . 2,572,997.76 / ha and Rp 4,568,517.01 / ha .   Keywords : subsidie, profit, season